The impact of oil price on Malaysia’s Gross Domestic Product (GDP) / Saiful Azlan Abu Hassan - Abu Hassan, Saiful Azlan (2011)
The end of the cold war, globalization, the rise of China and the rampant spread of information technology set the stage for a long spell of economic growth, high productivity, low inflation, and booming economy for not just the United States but for most of the rest of the world (Daniel Gross, 2007). The acceleration of the flow of workers across borders to the most competitive markets during the past decade has been a potent disinflationary force that not only held down wage growth but inflation in virtually every country. Yet this period of unprecedented worldwide economic growth coupled with low inflation may be at its end as the subprime and financial crisis has all but crippled the economy of the United States while commodity prices of both food and fuel has reached previously unforeseeable heights.